HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA GURU DI SEKOLAH DASAR SWASTA KECAMATAN KOTO TANGAH PADANG - Fitri Rahayu (Universitas Negeri Padang, 2014)
This research about organizational culture and teacher performance, also to see the relationship between the two variables. Population are 90 teachers and 48 samples using proportional stratified random sampling technique. This research instrument is a questionnaire in the form of a Likert scale, a score of variable organizational culture 0.948 and teacher performance 0.937 that means instrument is reliable. Data were analyzed using product moment correlation, get rscore = 0.29> = 0.284 believed rtabel standard 95%. Research has come to the conclusion the relationship between organizational culture with the performance of teachers in private sector of junior school Koto Tangah Padang. Key word: budaya organisasi dan kinerja